Informe del Proyecto: La Red de las Américas para la Equidad en Salud [2022] - Red de las Américas para la Equidad en Salud (2022)
The report’s presentation outlines the purpose of informing the Interinstitutional Committee for System Coordination and Evaluation (CICES) about the progress, findings, and recommendations from the Health Equity Action Network (RAES) within its institutional activities. It highlights intersectoral efforts to strengthen health equity, the analysis of key indicators, and technical proposals to improve coordination among system stakeholders. The presentation also situates the report within the 2022 evaluation cycle and previews the annexes that support the data and recommendations.